The Effect of Degeneration on Internal Strains and the Mechanism of Failure in Human Intervertebral Discs Analyzed Using Digital Volume Correlation (DVC) and Ultra-High Field MRI - Tavana, Saman; Masouros, Spyros D.; Baxan, Nicoleta; Freedman, Brett A.; Hansen, Ulrich N.; Newell, Nicolas (Frontiers in Bioengineering and Biotechnology, 2021)
The intervertebral disc (IVD) plays a main role in absorbing and transmitting loads within the spinal ‎column. Degeneration alters the structural integrity of the IVDs and causes pain, especially in the ‎lumbar region. The objective of this study was to investigate non-invasively the effect of ‎degeneration on human 3D lumbar IVD strains and the mechanism of spinal failure using digital ‎volume correlation (DVC) and 9.4 Tesla magnetic resonance imaging (MRI). Degenerate IVDs had ‎higher (p<0.05) axial strains (58% higher), maximum 3D compressive strains (43% higher), and ‎maximum 3D shear strains (41% higher), in comparison to the non-degenerate IVDs, particularly in ‎the lateral and posterior annulus. In both degenerate and non-degenerate IVDs, peak tensile and shear ‎strains were observed close to the endplates. Inward bulging of the inner annulus was observed in all ‎degenerate IVDs causing an increase in the AF compressive, tensile, and shear strains at the site of ‎inward bulge, which may predispose it to circumferential tears (delamination). The endplate is the ‎spine’s “weak link” in pure axial compression, and the mechanism of human vertebral fracture is ‎associated with disc degeneration. In non-degenerate IVDs the central region was observed to have a ‎high risk of fracture, whereas peripheral regions were more susceptible in degenerate IVDs. These ‎findings advance the state of knowledge on mechanical changes during degeneration of the IVD, ‎which help reduce the risk of injury, optimise treatments, and improve spinal implant designs. ‎Additionally, these new data can be used to validate computational models.‎